Representações de interdisciplinaridade por professores da rede pública ao longo de uma formação continuada - Brum, Maísa Helena (2015)
The interdisciplinary perspective at the school context has been very much under discussions and researches in Applied Linguistics. Several official educational documents of the Brazilian government, such as Orientações Curriculares Nacionais (OCNS) and Pârametros Curriculares Nacionais (PCNs) have mentioned the importance of an interdisciplinary practice in the classroom. Considering this background, this study aims to investigate the representations of interdisciplinarity during the construction of a pedagogical project within a continuing education program developed with teachers of a primary and adult education (EJA) public school in Santa Maria, RS. Furthermore, this research seeks to identify, considering the teachers discourse, their representations of interdisciplinarity and interdisciplinary practices. The corpus was collected through two questionnaires (the product of this research) that were answered, respectively, at the beginning and at the end of the program, which had the objective to identify the teachers representations of interdisciplinarity. Besides the questionnaires, the corpus was also constituted by transcripts from six (6) reflective sessions carried out during 2012 (the process of this research), in order to discuss the concept of interdisciplinarity and to develop the interdisciplinary project. Regarding the research s product, from a comparative analysis of the questionnaires, we noticed a change in the teachers representations of interdisciplinarity. In the initial questionnaire, the teachers conceptualize interdisciplinarity as an interaction between disciplines, which still refers to an interdisciplinary perspective of juxtaposition of content. At the end of the program there is an expansion in the teachers representation of interdisciplinary as a socially situated practice based on the interaction between different areas of knowledge, which present a common objective. Thus, the final representations unveil a more elaborated definition (Bernstein, 1996, p. 159) and a conceptual appropriation of teachers own pedagogical practice based on an interdisciplinary perspective. The research process revealed a sequence of discourse actions triggered by Problematization, followed mainly by Acceptance, Simple Exposition and Mirroring that shaped the construction of the interdisciplinary project at school while mediating the interactions between participants. In this sense, the argumentative process developed in the reflective sessions also assisted teachers organization of ideas, taking positions, and consequently, the development of a reflective thinking. Considering the representation of interdisciplinarity identified during the reflection sessions, we noticed an alignment with the final representations identified in the questionnaires, as both signal interdisciplinary practices as exchange of ideas between different disciplines with a common goal. Finally, we hope that the consolidation of the interdisciplinary project became part of their educational practices in that context. Likewise, we hope that the actions developed at the school context can lead to other studies that focus on the research of interdisciplinary practices, and, as a consequence, to foster new initiatives of continuing education programs for teachers (SILVA, 2014, p. 130).